Analytic Model for Conduction Current in AlGaN/GaN HFETs/HEMTs - Danqiong Hou; Griff L. Bilbro; Robert J. Trew (Active and Passive Electronic Components)
We have developed a new, zone-based compact physics-based AlGaN/GaN heterojunction field-effect transistor (HFET) model suitable for use in commercial harmonic-balance microwave circuit simulators. The new model is programmed in Verilog-A, an industry-standard compact modeling language. The new model permits the dc, small-signal, and large-signal RF performance for the transistor to be determined as a function of the device geometric structure and design features, material composition parameters, and dc and RF operating conditions. The new physics-based HFET model does not require extensive parameter extraction to determine model element values, as commonly employed for traditional equivalent-circuit-based transistor models. The new model has been calibrated and verified. We report very good agreement between simulated and measured dc and RF performance of an experimental C-band microwave power amplifier.